\(\left(2x+2\right)\left(x-3\right)=0\)
\(\Leftrightarrow2\left(x+1\right)\left(x-3\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x+1=0\\x-3=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=-1\\x=3\end{cases}}\)
Vậy \(x=-1;3\)
\(\left(2x+2\right)\left(x-3\right)=0\)
\(\Rightarrow2\left(x+2\right)\left(x-3\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x+2=0\\x-3=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-2\\x=3\end{cases}}}\)
Từ đề bài suy ra hai trường hợp nhé 2x+2=0 hoặc x-3=0. Còn lại bạn giải tiếp
CHÚC BẠN HỌC TỐT